Anxiety related to COVID-19 among Pregnant Women Visiting a Tertiary Hospital: A Descriptive Cross-sectional Study - Silwal, Ajita; Bhetwal, Jyoti; Ojha, Bijay (Journal of Karnali Academy of Health Sciences, 2021)
Background: The ongoing COVID-19 pandemic affected nearly all the people around the globe including Nepal. The increasing number of COVID-19 infections and related mortality has caused excessive worries and concerns among pregnant women. The profound stress and anxiety in pregnancy have significant relation with mental disorders, emotional problems as well as obstetric complications including preeclampsia, preterm deliveries, intrauterine growth restriction, low birth weight, caesarean birth, etc. The objective of this study was to find out the anxiety related to COVID-19 among pregnant women. Methods: A descriptive cross-sectional study was conducted among pregnant women attending a tertiary hospital in Kathmandu, Nepal. A total of 338 pregnant women were face-to-face interviewed using a structured questionnaire. Anxiety related to COVID-19 was measured using a validated Nepali version of the Beck Anxiety Inventory. The data were analyzed using Statistical Package for the Social Sciences (SPSS) version 18. Results: The anxiety related to COVID-19 was found in 52.1% of pregnant women. The majority of the pregnant women (79.54%) had minimal anxiety whereas none of them had severe form of anxiety. The anxiety was higher (including much, very much) in regards to the health of the fetus and delivery of the baby. Conclusions: Although the study showed the prevalence of anxiety in majority of the pregnant women, the level of anxiety was not intense as compared to the studies done in other countries.